2021
DOI: 10.1002/jper.20-0839
|View full text |Cite
|
Sign up to set email alerts
|

A re‐evaluation of scaling and root planing

Abstract: Background Extensive reviews on the role of scaling and root planing (SRP) in the treatment of periodontitis have been previously published. This commentary will address the importance of subgingival calculus in the progression and treatment of periodontitis and addresses factors that make the execution of a “definitive” SRP a critical part of therapy. Methods A search for articles, using keywords relevant to the subject , (e.g., periodontitis, dental scaling, root planing, dental calculus, biofilm, inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 44 publications
0
65
1
1
Order By: Relevance
“…However, the presence of bacteria was only regarded as the initiating factor. Indeed, the pathogenesis of periodontitis involves several molecules of the immune system that interact in a network to eliminate the pathogens, themselves contributing to noticeable damage in the whole apparatus of the periodontium [ 56 , 57 ]. Within the progression of periodontitis, there is high expression of proinflammatory cytokines such as interleukin IL-1β, IL-6, IL-8, tumor necrosis factor (TNF)-α and regulatory cytokines such as IL-4.…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of bacteria was only regarded as the initiating factor. Indeed, the pathogenesis of periodontitis involves several molecules of the immune system that interact in a network to eliminate the pathogens, themselves contributing to noticeable damage in the whole apparatus of the periodontium [ 56 , 57 ]. Within the progression of periodontitis, there is high expression of proinflammatory cytokines such as interleukin IL-1β, IL-6, IL-8, tumor necrosis factor (TNF)-α and regulatory cytokines such as IL-4.…”
Section: Resultsmentioning
confidence: 99%
“…The gold standard in the therapy of periodontitis is the mechanical subgingival instrumentation [ 10 ], although due to the complex anatomy of periodontal pockets and teeth, this procedure is unable to fully eradicate bacterial biofilms. The use of systemic antimicrobials is controversial and limited to aggressive and severe forms of periodontitis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated a strong relationship between subgingival calculus and periodontal inflammation [ 278 , 279 , 280 ]. Therefore, scaling and tooth root debridement for removal of calculus is the therapy of choice regarding PD [ 281 ], and procedures with ultrasound systems for comfortable patient therapy are more popular [ 282 ].…”
Section: Calculusmentioning
confidence: 99%